2018
DOI: 10.1021/acs.est.8b01796
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone-Disrupting Potentials of Major Benzophenones in Two Cell Lines (GH3 and FRTL-5) and Embryo-Larval Zebrafish

Abstract: Benzophenones (BPs) have been widely used in personal care products (PCPs) such as UV protectants. Sex endocrine-disrupting effects have been documented for some BPs, but, significant knowledge gaps are present for their thyroid-disrupting effects. To investigate the thyroid-disrupting potential of BPs, a rat pituitary (GH3) and thyroid follicle (FRTL-5) cell line were employed on six BPs, i.e., benzophenone (BP), benzophenone-1 (BP-1), benzophenone-2 (BP-2), benzophenone-3 (BP-3), benzophenone-4 (BP-4), and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 57 publications
7
34
0
Order By: Relevance
“…The results of correlation analysis also support the essential roles of the transcription of the trh, tshβ, and tshr genes in thyroid hormone regulation. The upregulation of tshβ and tshr genes by exposure to avobenzone and octinoxate observed in this study is similar to that of previous studies that reported elevation of TSH-related genes by BPs and octinoxate (Chu et al 2021;Lee et al 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of correlation analysis also support the essential roles of the transcription of the trh, tshβ, and tshr genes in thyroid hormone regulation. The upregulation of tshβ and tshr genes by exposure to avobenzone and octinoxate observed in this study is similar to that of previous studies that reported elevation of TSH-related genes by BPs and octinoxate (Chu et al 2021;Lee et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, downregulation of the trαa and trβ genes in sh larvae exposed to avobenzone and octinoxate may also suggest possible activities to inhibit thyroid hormone receptor binding. The observation of higher mortality in thrαa −/− than in wild-type sh is interesting, given that BPs and octinoxate have been reported to inhibit receptor binding capacity in previous studies (Chu et al 2021;Lee et al 2018). Our observation also supports the central role of the thyroid hormone receptor in the toxicity of avobenzone and octinoxate.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Triiodothyronine (T3) was found to be positively associated with risk factors for GDM [39]. An animal study indicated that BP-3 could down-regulate genes related to thyroid stimulating hormones with significant decreases in T3 levels [40], and similar associations were found among pregnant women [41]. Therefore, it is possible that exposure to BP-3 could lead to decreased level of T3 and decreased GDM risk, potentially via decreasing endogenous glucose production and plasma glucose [42].…”
Section: Discussionmentioning
confidence: 96%
“…All but one displayed estrogenic activity [174]. As regards the thyroid axis, in vitro studies showed five benzophenones to significantly to decrease expression of thyroid-responsive genes [175]. The same study showed benzophenone-1, benzophenone-3 and benzophenone-8 to decrease thyroid hormone levels in an animal model.…”
Section: Benzophenonesmentioning
confidence: 87%